Pattern of Substance Abuse in Northwestern Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Available information indicates that substance abuse poses a major political, social, and health challenge worldwide. Availability of drugs, negative peer pressure, poverty, and frustration are among the factors that increase the burden of substance abuse. Urine drug testing (UDT) is a reliable laboratory method of analyzing substances of abuse because many drugs and their metabolites remain detectable in the urine for longer periods.Aims:To detect the laboratory pattern of substance abuse among youths in North-Western Nigeria and to make recommendations based on the overall pattern to curtail the effect on society.Settings and Design:A retrospective cross-sectional survey of secondary data of patients who presented to a clinical laboratory for urine drug tests.Methods and Material:Trained personnel carried out a supervised collection of fresh urine samples, which were analyzed using a qualitative immunoassay technique. The presence of a drug was determined by reaching the drug’s limit of detection.Statistical Analysis Used:Data were analyzed using a Statistical Package for the Social Science (SPSS) version 2 software.Results:The screen prevalence of substance abuse was 60.9%. Among those who tested positive, 97% were males, whereas 3% were females. The majority of participants were youths below 30 years of age. The observed pattern revealed a few of the participants (26.48%) had only one drug substance present in their urine, whereas 73.53% tested positive for multiple substances ranging from two to five drugs in a urine sample.Conclusion:A high prevalence of substance abuse was observed and most of the participants were multidrug users.